1995
DOI: 10.1007/bf00618490
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid function in cardiac transplant patients: evaluation during physical exercise

Abstract: The survival rate of heart transplant patients has increased considerably since the development of new immunosuppressive drugs. In the long term, however, cardiac transplantation results in a high incidence of osteoporosis which represents a major functional handicap. To examine whether patients in the early stages have impaired phosphocalcic metabolism, intact parathyroid hormone (PTH 1-84), native osteocalcin, ionized Ca++ and pH were measured at rest and during muscular exercises a dynamic test used to over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
2
1
Order By: Relevance
“…As reported in a previous study (Brandenberger et al 1995), we have observed that basal concentrations and exercise-induced variations of PTH are signi®cantly higher in HTR than in healthy subjects. Whether this sustained, albeit moderate, hyperparathyroidism can contribute to long-term bone loss in HTR needs to be clari®ed.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…As reported in a previous study (Brandenberger et al 1995), we have observed that basal concentrations and exercise-induced variations of PTH are signi®cantly higher in HTR than in healthy subjects. Whether this sustained, albeit moderate, hyperparathyroidism can contribute to long-term bone loss in HTR needs to be clari®ed.…”
Section: Discussionsupporting
confidence: 61%
“…This increase of Ca 2+ during exercise should theoretically induce a decrease of PTH. These simultaneous rises of Ca 2+ and PTH that we and other authors have observed (Nishiyama et al 1988;Henderson et al 1989;Ljunghall et al 1994;Salveson et al 1994;Brandenberger et al 1995) are paradoxical. The increase in PTH could be due at least partly to haemoconcentration.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations